Analysis Of Presumed Land Subsidence In The Cities Of Lampung Province Using InSAR And GNSS Data - Alif, Satrio Muhammad; Anggara, Ongky; Perdana, Redho Surya; Hasannah, Uswatun; Azizah, Fadhillah Nur (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Land subsidence is a naturally occurring phenomenon that has become a growing concern in various regions, including Lampung Province. In this study, we investigate land subsidence in various cities within Lampung Province, Indonesia, utilizing Sentinel-1A using Sentinel-1A satellite image data from the period 2014 to 2022. The cities of Lampung Province analyzed in this study were Liwa, Kota Agung, Kalianda, Sukadana, Bandar Lampung and Krui. The method used is Interferometric Synthetic Aperture Radar (InSAR) with the Small Baseline Area Subset (SBAS) technique. Furthermore, to validate and improve the accuracy of land subsidence measurements, the Global Navigation Satellite System (GNSS) velocities were utilized. The land subsidence result obtained in this study is presumed land subsidence. The cities that experienced land subsidence was Kalianda, Sukadana, Bandar Lampung and Krui ranging from ~3 mm/yr to ~15 mm/yr. Meanwhile, the areas that experienced an uplift were the Liwa and Kota Agung cities.